Assessment of risks for the gas industry in Russia in the context of the formation of a common gas market of the Eurasian Economic Union - Marina F. Tkachenko; Nelia I. Allaiarova (RUDN Journal of Economics, 2021)
The research aimed to identifies the risks for the development of the gas industry in Russia in the context of the emerging common gas market of the EAEU. The state of the gas industry in Russia and Russias cooperation with the EAEU member states in the gas sector are considered. The development of the Russian gas industry is determined both by the dominant position of the vertically integrated natural monopoly PJSC Gazprom, and by the characteristics of the global hydrocarbon energy market. Based on empirical data, it is concluded that the creation of a common gas market in the EAEU is not only a challenge to the development of the Russian gas industry, but also a measure to strengthen and expand its positions in the global energy market, increase the efficiency of participation in the global energy agenda, as well as an incentive for improving the domestic gas market in Russia.